2004
DOI: 10.2169/internalmedicine.43.374
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Artery Systolic Pressure is Elevated in the Elderly: Relationships between Echocardiographic and Pathological Findings

Abstract: Objective We investigated the relationship between the right cardiac system and increased pulmonary artery systolic pressure (PASP) in the elderly.Patients and Methods Echocardiography stable state data were available for 163 of 200 consecutive autopsied patients. Of these, PASP could be estimated by extrapolation from the maximum pressure gradient in tricuspid valve regurgitation from echocardiograms in 73 cases; however, 22 cases with secondary changes attributable to left cardiac insufficiency had to be exc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…And besides, previous studies demonstrated some hemodynamic changes elevating RLS in elderly patients, the promoting pulmonary-arterial pressure for instance, could contribute to a higher possibility of PTE (Homma, DiTullio, Sacco, Sciacca, & Mohr, 2004;Ueda et al, 2004). We speculated that the importance of PFO in the pathogenesis of stroke was more obvious in aged patients.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…And besides, previous studies demonstrated some hemodynamic changes elevating RLS in elderly patients, the promoting pulmonary-arterial pressure for instance, could contribute to a higher possibility of PTE (Homma, DiTullio, Sacco, Sciacca, & Mohr, 2004;Ueda et al, 2004). We speculated that the importance of PFO in the pathogenesis of stroke was more obvious in aged patients.…”
Section: Discussionmentioning
confidence: 83%
“…In addition, the prevalence of venous thrombosis and pulmonary embolism (Stollberger et al, ), as well as the presence of concomitant atrial septum aneurysm (Handke, Harloff, Bode, & Geibel, ), which may act as important risk factors of PTE when coexistence with PFO (Mas et al, ; Stollberger et al, ), would also increase with age. And besides, previous studies demonstrated some hemodynamic changes elevating RLS in elderly patients, the promoting pulmonary–arterial pressure for instance, could contribute to a higher possibility of PTE (Homma, DiTullio, Sacco, Sciacca, & Mohr, ; Ueda et al, ). We speculated that the importance of PFO in the pathogenesis of stroke was more obvious in aged patients.…”
Section: Discussionmentioning
confidence: 95%
“…68 Konstantinides et al found a significantly elevated risk of death and arterial embolisms in patients with pulmonary embolism and PFO. 69 The pulmonary-arterial pressure is higher in older than in younger patients 70 and thus probably also the risk of thrombus passage across a PFO.…”
Section: Paradoxical Embolism In Older Patients: Pathophysiological Pmentioning
confidence: 99%
“…In a study investigating the relationship between PAPs and age, Ueda et al [12] in healthy aged subjects found an increased value compared with that recorded in younger healthy subjects. This different behaviour seems to be reported to the changes of the senile lungs, characterized by a homogeneous enlargement of the alveolar airspaces without fibrosis or destructions of alveolar walls [13,14].…”
Section: Introductionmentioning
confidence: 88%